Separation of mediastinal shed blood during aortic valve surgery elicits a reduced inflammatory response. Issue 1 (January 2016) - Bisleri, Gianluigi; Tononi, Laura; Morgan, Jeffrey A.; Bordonali, Tania; Cheema, Faisal H.; Siddiqui, Osama T.; Repossini, Alberto; Rosati, Fabrizio; Muneretto, Claudio
Abstract : Aims: The detrimental effects of inflammation following cardiopulmonary bypass (CPB) could negatively affect the postoperative outcome in a specific subset of high-risk patients. We therefore investigated the impact of a CPB circuit (Admiral, Eurosets, Italy) that allows separation of intracavitary and mediastinal blood on the release of biochemical markers and clinical outcome when compared with a conventional circuit. Methods: Thirty patients undergoing aortic valve surgery were prospectively enrolled and assigned to Admiral group (Group 1, G1, n  = 15) or conventional CPB group (Group 2, G2, n  = 15). The Admiral oxygenator allows for a separate collection of mediastinal blood processed through a cell-saver before retransfusion. Clinical data and biochemical parameters were measured preoperatively, during CPB and at different time-points postoperatively. Results: Preoperative demographics, intraoperative data (as CPB and aortic cross-clamping time) and perioperative complications did not differ between groups. Inflammatory response was significantly decreased in G1, as assessed by means of D-dimer (G1 = 1332.3 ± 953.9 vs. G2 = 2791.9 ± 1740.7 ng/ml, P  = 0.02), C-reactive protein (G1 = 169.1 ± 164.8 vs. G2 = 57.1 ± 39.3 mg/l, P  = 0.04), interleukin-6 (G1 = 11.8 ± 12.5 vs. G2 = 26.5 ± 24.9 pg/ml, P  = 0.02) and tumour necrosis factor-alpha (G1 = 29 ± 28.7 vs. G2 = 45.5 ± 23.6 pg/ml, P  = 0.03). Conclusion: Although no considerable difference was detected in terms of perioperative outcomes, the Admiral oxygenator did result in a significant reduction of inflammatory markers during the early postoperative course.